Preaching as "Commercialised Pavement Spirituality" : Towards a Streetwise Ecclesiology of "Spaza Faith" (mens-kerk) - Louw, Daniël (Stellenbosch Theological Journal, 2019)
The Africanisation of Christianity is indeed a challenging endeavour. It is difficult to pin point what is exactly meant by an African version of the Christian faith. Many attempts to make Christianity "indigenous" are merely a European version with an African flavour. The article probes into the informal life settings of township spirituality. Unemployment and poverty demarcate the structural conditions of township life. The phenomenon of spaza entrepreneurship is investigated, specifically how naming of informal street businesses, often reflects a kind of internalised Christian spirituality. Spaza is the Zulu word for camouflage. With "spaza" piety is meant: Faith in Cognito; faith operating within the disguise of faithful businesses where poor and unemployed people try to survive the hardships of poverty and unemployment. "Spaza spirituality" is rendered as a kind of streetwise "sermon". At stake within the discipline of homiletics is the following questions: When the context becomes the text, what is meant by "contextual preaching" within township life? Can the Christian faith indeed beautify township life so that practical theology implies more than ethical endeavours but includes an aesthetic ecclesiology: Fides quaerens beatitudinem (faith seeking the beautification of life).